18F-FDG PET/CT Findings of an Isolated Splenic Metastasis From Endometrial Adenocarcinoma. (December 2020) - Xu, Tingting; Cen, Bing; Liu, Lin; Wang, Yingwei; Chen, Yue
Abstract : Abstract: Splenic metastasis from endometrial carcinoma is rare, especially when the spleen is the sole metastatic site. Herein, we report the case of a 47-year-old woman with a history of endometrial adenocarcinoma diagnosed 1 year ago. At that time, she underwent total abdominal hysterectomy, bilateral salpingo-oophorectomy, and pelvic node dissection. Restaging 18 F-FDG PET/CT demonstrated an isolated splenic mass with elevated FDG activity. There were no other signs of recurrence. The lesion was surgically resected and diagnosed as a metastasis from the endometrial adenocarcinoma.